Catalytic/Protective Properties of Martian Minerals and Implications for Possible Origin of Life on Mars - Fornaro, Teresa (Life (Basel), 2018)
Minerals might have played critical roles for the origin and evolution of possible life forms on Mars. The study of the interactions between the “building blocks of life” and minerals relevant to Mars mineralogy under conditions mimicking the harsh Martian environment may provide key insight into possible prebiotic processes. Therefore, this contribution aims at reviewing the most important investigations carried out so far about the catalytic/protective properties of Martian minerals toward molecular biosignatures under Martian-like conditions. Overall, it turns out that the fate of molecular biosignatures on Mars depends on a delicate balance between multiple preservation and degradation mechanisms, often regulated by minerals, which may take place simultaneously. Such a complexity requires more efforts in simulating realistically the Martian environment in order to better inspect plausible prebiotic pathways and shed light on the nature of the organic compounds detected both in meteorites and on the surface of Mars through in situ analysis.